(untitled) (Research, Society and Development, 2022)
Experts have speculated the potential of heparin administration as COVID-19 treatment modality, although scientific research regarding its effectivity, recommended dosage, and period are still minimal. This study aims to explore the capacity of LMWH as a medicament for COVID-19, in effort to provide scientific reference for further development of COVID-19 possible choice of treatment or medicament. A retrospective study was conducted in Udayana University Hospital, Bali, Indonesia. Data were sourced from laboratory-confirmed COVID-19 patients medical records during March 25 to July 31, 2020. Clinical, laboratory, treatment and use of LMWH data were reviewed and statistically processed. 42 patients we found Use of LMWH. The patient categorizes from moderate to severe COVID-19. 31 patients use of LMWH for prophylaxis and 11 patients use of LMWH for treatment. 7 patients were death in the hospital, and the other was survived. LMWH elevates coagulation dysfunction in COVID-19 patients. We believe that beneficial effects of LMWH as prophylaxis or treatment in COVID-19 patients.